1997
DOI: 10.1128/mcb.17.9.5165
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Maize Mutator Transposable Element MURA Transposase as a DNA-Binding Protein

Abstract: The autonomous MuDR element of the Mutator (Mu) transposable element family of maize encodes at least two proteins, MURA and MURB. Based on amino acid sequence similarity, previous studies have reported that MURA is likely to be a transposase. The functional characterization of MURA has been hindered by the instability of its cDNA, mudrA, in Escherichia coli. In this study, we report the first successful stabilization and expression of MURA in Saccharomyces cerevisiae. Gel mobility shift assays demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 56 publications
0
84
0
Order By: Relevance
“…Interestingly, given the total lack of MURB-related sequences in the databases, no sequences similar to TnsE are found among Tn7 relatives in other bacteria. In the absence of JITB, JITA would still bind to sites in the Jit TIRs, analogous to the MURA binding sites found in the MuDR TIRs (Benito and Walbot, 1997), and make staggered cuts in the DNA immediately adjacent to the transposon ends. However, the resulting double-strand break would be subsequently repaired without footprint formation by the action of an endogenous ligase present in all maize lines, and, in the absence of a cleaved receptor site, Jit would fail to reinsert in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, given the total lack of MURB-related sequences in the databases, no sequences similar to TnsE are found among Tn7 relatives in other bacteria. In the absence of JITB, JITA would still bind to sites in the Jit TIRs, analogous to the MURA binding sites found in the MuDR TIRs (Benito and Walbot, 1997), and make staggered cuts in the DNA immediately adjacent to the transposon ends. However, the resulting double-strand break would be subsequently repaired without footprint formation by the action of an endogenous ligase present in all maize lines, and, in the absence of a cleaved receptor site, Jit would fail to reinsert in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results also suggest that the transposition of each MULE subclass is under a different regulation. The MURA transposase binding site (MBS), a 32-bp motif in the TIRs, is well conserved among the mobile Mutator elements (Benito and Walbot 1997;Rudenko and Walbot 2001). It was suggested that transposase active for transposition of subclass II MoTUs might not be able to recognize MBSs of subclass I MoTUs.…”
Section: Copy Number Variation Of Mules In Wheatmentioning
confidence: 99%
“…MuDR carries two genes, mudrA and mudrB. The former encodes the MURA transposase that catalyzes the excision of Mutator (Eisen et al 1994;Benito and Walbot 1997) and the latter encodes the MURB protein that is proposed to be involved in the reinsertion of Mutator (Lisch et al 1999;Raizada and Walbot 2000). However, the sequence corresponding to mudrB has only been identified in the genus Zea so far (Lisch et al 1995;Walbot and Rudenko 2002).…”
Section: Introductionmentioning
confidence: 99%
“…MuDR contains two protein-coding genes: mudrA encodes MURA transposase and mudrB encodes MURB helper proteins functioning in the Mu insertional activity (Lisch et al, 1999;Raizada and Walbot, 2000). All Mu elements share ~215-bp terminal inverted repeat (TIR) sequences, and the mobile Mu elements contain a highly conserved 32-bp MURA transposase binding site within both TIRs (Benito and Walbot, 1997). Only a few maize lines contain active MuDR elements, but all maize lines examined carry homologous MuDR sequences (hMuDR elements; Rudenko and Walbot, 2001).…”
Section: Introductionmentioning
confidence: 99%